Evaluasi Penyelenggaraan Pelatihan Produktivitas di UPT BLP2TK Jawa Timur dalam Menghadapi Era Digital Marketing - Charira, Churil Akyun Giant; Nafiah, Binti Azizatun (VISA: Journal of Vision and Ideas, 2025)
This study evaluates the implementation of productivity training by the East Java Productivity and Manpower Development Training Center (UPT BLP2TK) in facing the digital marketing era, with a focus on increasing the competitiveness of MSMEs. The approach used is a descriptive qualitative method. The data collection techniques used in this research are (1) questionnaire, (2) in-depth interviews, (3) observation, and (4) literature study/desk research, and the population in this research are registered MSME actors in the city of Surabaya. The results of the study indicate that the most frequently implemented quality and productivity improvement programs include improving work processes and HR education and training, because the costs are relatively affordable. The program implementation model is more often carried out independently or through government agency guidance compared to private institutions or central companies. These programs have a significant impact, such as increasing work enthusiasm, product quality, and sales turnover. However, the impact on cost savings and on-time delivery is still less felt. The main obstacles in implementing this program include budget constraints and the lack of consistency in implementing productivity improvement activities. This study recommends strengthening the provision of digital marketing training to increase the competitiveness of MSMEs in the digital era, including an emphasis on simple financial management to maximize cost efficiency and productivity in a sustainable manner.